2018
DOI: 10.4103/jnrp.jnrp_189_17
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Sleep and Sleep Disorders in Patients with Parkinsonism: A Polysomnography Based Study from Rural South India

Abstract: Objective:The objective of this study is to study the quality of sleep, sleep disorders, and polysomnographic profile in Parkinsonism patients from rural areas and to correlate polysomnographic profile with the staging of disease and with sleep questionnaire.Materials and Methods:Between May 2014 and December 2015, 168 Parkinsonism patients were prospectively screened using sleep questionnaire; Epworth Sleepiness Scale (ESS), Pittsburgh Sleep Quality Index (PSQI), Parkinson Disease Sleep Score-2 (PDSS-2). Sixt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 35 publications
(42 reference statements)
3
11
0
Order By: Relevance
“…Among the subsequent manifest HD population, sleep abnormalities appear to continue to progress in parallel with increasing disease severity [ 44 , 57 , 60 ]. Again this mirrors findings in Alzheimer’s and Parkinson’s [ 61 , 62 ].…”
Section: Sleep and Circadian Abnormalities In Huntington’s Disease: Evidence To Datesupporting
confidence: 80%
See 1 more Smart Citation
“…Among the subsequent manifest HD population, sleep abnormalities appear to continue to progress in parallel with increasing disease severity [ 44 , 57 , 60 ]. Again this mirrors findings in Alzheimer’s and Parkinson’s [ 61 , 62 ].…”
Section: Sleep and Circadian Abnormalities In Huntington’s Disease: Evidence To Datesupporting
confidence: 80%
“…This has revealed that fragmentation appears to be an important component of HD sleep architectural disturbance, including in the premanifest phase. Once again this parallels findings in Alzheimer's and Parkinson's, where sleep fragmentation in particular has been identified as a feature of both premonitory and established disease [62][63][64][65][66].…”
Section: Sleep Architecture Abnormalitiessupporting
confidence: 71%
“…The PDSS-2 is designed to assess sleep disorders and other nocturnal symptoms in patients with PD and is an easy, valid, and reliable scale, which may be useful for measuring treatment responses [ 14 ]. Moreover, it has been found to correlate positively with polysomnographic parameters [ 33 ]. In this study, the cutoff of total score ≥ 15 was employed to identify significant ND.…”
Section: Discussionmentioning
confidence: 99%
“…20 In healthy adults discrepancy between subjective and objective measures of sleep is usually reported, but in PD patient, the positive correlation between these measures is reported more frequently. 21 In general, the PD patients often attribute their poor sleep quality to insomnia. 22 In this framework, decrease of sleep duration and sleep efficiency that is observed with the advance of Parkinson's disease, may be due to the presence of symptoms of depression, motor fluctuations, hypokinesia and, importantly, to use high doses of dopamine agonists.…”
Section: Discussionmentioning
confidence: 99%